Removal of Pb(II) using Hydroxyapatite from Golden Snail Shell (Pomacea canaliculata L.) Modified with Silica - Poedji Loekitowati Hariani; Fahma Riyanti; Fatma Fatma; Addy Rachmat; Aldi Herbanu (Universitas Jenderal Soedirman, 2020)
The composites of hydroxyapatite and SiO2 were successfully synthesized. The hydroxyapatite was prepared from golden snail shells (Pomacea canaliculata L). The hydroxyapatite and hydroxyapatite-SiO2 composites were characterized using XRD, FTIR, SEM-EDS. Furthermore, hydroxyapatite and hydroxyapatite-SiO2 composites were used to remove Pb(II) from aqueous solution. Various adsorption parameters such as pH of the solution, contact time, and initial Pb(II) concentration were used to study the adsorption process. The optimum pH of the solution for removal of Pb(II) by hydroxyapatite and hydroxyapatite-SiO2 composite at pH 6 and contact time at 60 minutes. Both adsorbents follow the Langmuir isotherm. The maximum adsorption capacity of the hydroxyapatite-SiO2 composite is greater compare to hydroxyapatite, respectively 135.14 and 123.46 mg/g. The pseudo-second order kinetic model had a correlation coefficient (R2) greater than the pseudo-first order so pseudo-second order kinetic is better to describe adsorption kinetics